MAQASID SHARIA IMPLEMENTATION IN MONETARY POLICY: A Literature Study - Andri Soemitra; Rifki Ismal; Burhanuddin Al-Butary; Ismail Ismail; Arpizal Arpizal; Rijal Allamah Harahap (el-Amwal, 2021)
The Islamic economic system also contributes to the global economy, including in Indonesia. However, the extent to which the implementation of sharia maqasid in it still needs further research. This article tries to explore the extent of the implementation of maqasid sharia in monetary policy, especially in Indonesia. The methodology used is a literature study approach to 100 national and international journal articles, as well as books and other literature related to the implementation of the sharia maqasid. The main finding of this research is that Islamic maqasid is not only needed to formulate economic policies, both monetary, fiscal and financial policies, but also to create Islamic banking products and other real sectors